Metal-Organic Framework-Based Nanotherapeutics With Tumor Hypoxia-Relieving Ability for Synergistic Sonodynamic/Chemo-therapy - Zhong, Lichang; Yang, Tian; Li, Pei; Shi, Lin; Lai, JinYu; Gu, Liping (Frontiers in Materials, 2022)
Hypoxia, a hallmark of cancer, compromises the efficacy of chemotherapy and other oxygen-dependent modalities (e.g., sonodynamic therapy). For monotherapy, this effect becomes more pronounced because of drug resistance and an adaptive tumor microenvironment. To overcome this, here, we reported metal–organic framework (MOF)-based nanotherapeutics (DOX/Ce6@ZIF-8@PDA) to simultaneously deliver Ce6 and doxorubicin for synergistic sonodynamic/chemotherapy. Notably, O2 storage ability of MOFs relieves tumor hypoxia to sensitize the tumor to sonodynamic therapy and chemotherapy. Moreover, polydopamine (PDA) promotes endocytosis and enhances intracellular drug concentration. The pH-responsive property of MOFs enables controlled drug release. The in vitro and in vivo results validate the impressive tumor inhibition, implying the potential of this combination therapy for cancer treatment.